Bullying Prevention Through Classical Guidance Service With The Snowball Throwing Method - Tas'adi, Rafsel; ., Mudjiran; ., Nurhizrah Gistituati; Ananda, Azwar (KnE Social Sciences, 2023)
Recently, there are a lot of distressing cases that hit the education world conducted by students, such as brawls and bullying. It was committed by one or a group of children to their weak friend, which causes the victim physically and psychologically hurt. Bullying does not only occur at the junior and senior high school but also the elementary level. This kind of behavior has to be prevented. One thing that can be done is through classical guidance with the Snowball Throwing method. This is a one-shot case study with the subjects were 22 students of Elementary School No. 24 Lima Kaum. Data was collected by using observation technique then it was analyzed by using the descriptive qualitative method. The result that showed during the classical guidance is that students had a positive attitude to their friends like having teamwork, giving respond to friends‘ questions, delivering ideas confidently, and saying politely without harsh words. Having positive attitudes in friendship will avoid bullying. Keywords: Bullying; classical guidance; snowball throwing method